Characteristic differences between the brain networks of high-level shooting athletes and non-athletes calculated using the phase-locking value algorithm - Gong, A.; Liu, J.; Lua, L.; Wu, G.; Jiang, C.; Fu, Y. (Biomedical Signal Processing and Control, 2019)
Long-term professional sport training may cause the brain functional network of high-level athletes to differ significantly from that of non-athletes. To test this hypothesis, electroencephalograms (EEGs) from 20 high-level shooting athletes and 20 age- and gender-matched non-athletes are collected in an eyes-closed resting state. The frequency spectrum was divided into four bands according to the individual alpha frequency of each participant: delta, theta, alpha1, and alpha2. The phase-locking values of the EEG in each frequency band are calculated and graph theory is used to analyze the topology of the EEG brain functional network based on the phase-locking-value connection. The results show that, compared with non-athletes, high-level shooters have higher connectivity in the left-temporal region, left-posterior temporal region, left-frontal region, left-central region, and right-parietal region. The network-clustering coefficients and small-world characteristics of athletes in the theta and alpha1 bands are significantly greater than that of non-athletes. These results support the hypothesis that brain function coupling in high-level shooting athletes is more connected than that in non-athletes, and the brain networks of high-level athlete have stronger small-world characteristics than those of non-athletes.